2004
DOI: 10.1038/sj.bjc.6602033
|View full text |Cite
|
Sign up to set email alerts
|

Faecal tumour M2 pyruvate kinase: a new, sensitive screening tool for colorectal cancer

Abstract: Proliferating cells, especially tumour cells, express a special isoenzyme of pyruvate kinase, termed M2-PK, which can occur in a tetrameric form with a high affinity to its substrate, phosphoenolpyruvate (PEP), and in a dimeric form with a low PEP affinity. In tumour cells, the dimeric form is usually predominant and is therefore termed Tumour M2-PK. The levels of Tumour M2-PK within tumours and in EDTA-plasma correlate with staging and the ability of the tumour cells to metastasise. Since most colorectal tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 33 publications
9
97
2
2
Order By: Relevance
“…These analyses showed that performance characteristics of the test only changed slightly when potential degradation during mailing of control samples was taken into account. The consistency of our findings with performance characteristics reported previously based on smaller sample sizes (Hardt et al, 2004;Shastri et al, 2006) further supports that the limitations of our study might not have distorted the results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These analyses showed that performance characteristics of the test only changed slightly when potential degradation during mailing of control samples was taken into account. The consistency of our findings with performance characteristics reported previously based on smaller sample sizes (Hardt et al, 2004;Shastri et al, 2006) further supports that the limitations of our study might not have distorted the results.…”
Section: Discussionsupporting
confidence: 91%
“…Given that previous studies on tumour M2-PK did not mention conditions of sample handling at all (Hardt et al, 2004;Shastri et al, 2006), the necessity of raising stability issues within our study is not only a limitation, but also a strength and allows further conclusion: Application of the test in a setting where a cold chain might be feasible would be expected to result in levels of specificity close to the corrected levels derived in this study and in levels of sensitivity close to those observed in this study. Conversely, application of the test in a setting where all stool samples are mailed without cooling would be expected to result in levels of specificity close to the uncorrected levels observed in this study and in levels of sensitivity that would be somewhat lower than observed in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies investigating this test reported a comparably high sensitivity for CRC ranging about 70 -80%, whereas specificity ranged about 70 -90% (Hardt et al, 2004;Vogel et al, 2005;Shastri et al, 2006;Tonus et al, 2006;Haug et al, 2007;Mulder et al, 2007;Koss et al, 2008). However, the potential of the tumour M2 PK test to detect colorectal adenomas, an issue that is highly relevant for estimating its use in reducing CRC incidence and mortality, has been investigated rarely and with rather limited sample size only (Vogel et al, 2005;Shastri et al, 2006;Mulder et al, 2007;Koss et al, 2008).…”
mentioning
confidence: 99%
“…Fecal pyruvate kinase: Fecal Pyruvate Kinase has been suggested as a potential new marker for intestinal inflammation in children with IBD [75], a new predictor for inflammation and severity of pouchitis [76], and as a new, sensitive screening tool for CRC [77].…”
Section: Biomarkers Of Outcomes/complicationsmentioning
confidence: 99%